Should Children Be Victims of Their Future? (Reflections on the Implementation of Child Rights through Legal Terms) - Ikhsan, Edy; Rosmalinda (CENTRAL ASIA AND THE CAUCASUS, 2022)
A child is everyone who is in process of growing up being an adult. Through the process, children face various challenges that require supporting system their neighborhood such as culture. Currently, children are risky to become victim of violence including sexual violence. This study raises the question, how culture in the context of "using terms" for sexual violence would protect children? In order to find out the answer, this study used the literature review approach. The primary data sources are court decisions concerning sexual violence on children. Furthermore, it also used literatures concerning culture which support the measures to stop sexual violence against children in Indonesia. As findings, it shows that a) The use of the term for sexual violence against children in Indonesia cannot provide maximum protection for child victims; b) there are development in legal terms for sexual violence both internationally and regionally concerning sexual violence; c) Indonesian government has programs to protect child victims of sexual violence through the Child Friendly City program (Kota Layak Anak- KLA). Finally, this study suggests that Indonesian government either executive, legislative or judiciary should play an important role to achieve the principle of the best interests of children particularly for children who are victims of sexual violence in Indonesia